Legal Analysis of Criminal Responsibility of Joint Theft Perpetrators in Indonesian Criminal Law from the Perspective of Retributive Justice - Robert Devis Wattimena; Muhammad Ngazis (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This research is entitled “A Juridical Analysis of Criminal Liability of Perpetrators of Joint Theft in Indonesian Criminal Law from the Perspective of Retributive Justice (Case Study of Verdict Number 146/Pid.B/2025/PN.Ptk).” The study aims to analyze the criminal liability of perpetrators of theft committed jointly under Indonesian criminal law and to assess the extent to which the court’s verdict reflects the principles of retributive justice. The research method used is normative juridical research, which involves examining relevant legislation, legal doctrines, and court decisions. The results indicate that, first, criminal liability for joint theft is regulated under Article 363 paragraph (1) point 4 of the Indonesian Criminal Code (KUHP), which stipulates that every participant, whether as a principal actor or an accomplice, can be held criminally responsible. This is reflected in Verdict Number 146/Pid.B/2025/PN.Ptk, where the judges found Ardiansyah and Arik Saputra guilty of aggravated theft committed jointly, and both were sentenced to imprisonment. Second, the court’s decision reflects normative retributive justice because the punishment serves as a proportional response to the offenders’ wrongdoing. However, from the perspective of proportional retributive justice, the verdict is not entirely fair, as it does not differentiate the roles and degrees of culpability of each perpetrator. Third, an ideal application of criminal liability should be based on the principle of individualized sentencing, which imposes punishment according to each defendant’s contribution and role. Accordingly, Ardiansyah, as the main executor who broke the glass and took the electronic items, should receive a harsher sentence than Arik Saputra, who only guarded outside and facilitated the escape.